Pengaruh Harga, Promosi dan Lokasi terhadap Kepuasan Pelanggan dengan Keputusan Pembelian Sebagai Variable Intervenning - Rizka Paramitha Aniqi; Nanto Purnomo (BISMA : Business and Management Journal, 2025)
This study aims to analyze the influence of price, promotion, and location on customer satisfaction, with purchasing decisions as an intervening variable at the Bintang Muda Sport Store in Lamongan. The research method used is quantitative with a descriptive approach. Data collection was conducted by distributing questionnaires to 150 store customers. The analysis tool used was Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach. The results show that price, promotion, and location have a direct and significant influence on customer satisfaction and purchasing decisions. Purchasing decisions also proved to be an intervening variable that strengthens the relationship between the independent variables and customer satisfaction. These findings are expected to provide strategic input for the store in improving service quality and customer satisfaction.